2008
DOI: 10.4161/auto.6477
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy protects renal tubular cells against cyclosporine toxicity

Abstract: A major side effect of the powerful immunosuppressive drug cyclosporine (CsA) is the development of a chronic nephrotoxicity whose mechanisms are not fully understood. Recent data suggest that tubular cells play a central role in the pathogenesis of chronic nephropathies. We have shown that CsA is responsible for endoplasmic reticulum (ER) stress in tubular cells. Autophagy has recently been described to be induced by ER stress and to alleviate its deleterious effects. In this study, we demonstrate that CsA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
138
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(144 citation statements)
references
References 31 publications
5
138
0
1
Order By: Relevance
“…Ischemic, toxic, immunological, and oxidative insults can cause an induction of autophagy in renal epithelial cells, modifying the course of various kidney diseases (41)(42)(43)(44). The effects of autophagy on the regulation of innate and adaptive immunity and cell viability are particularly relevant in transplanted tissue, which faces a great number of stresses that challenge its viability and immunogenicity (9).…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic, toxic, immunological, and oxidative insults can cause an induction of autophagy in renal epithelial cells, modifying the course of various kidney diseases (41)(42)(43)(44). The effects of autophagy on the regulation of innate and adaptive immunity and cell viability are particularly relevant in transplanted tissue, which faces a great number of stresses that challenge its viability and immunogenicity (9).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is increasingly appreciated as a protective mechanism against the progression of certain human diseases (18) and recent studies implicate a cytoprotective role of autophagy in kidney injury (31,32). CO is an endogenous product of heme oxygenase activity that has been shown to exert potent cytoprotection against tissue injury including kidney fibrosis (34), and recently CO has been shown to induce autophagy (48).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy also plays an important role in cellular defense mechanism to certain pathogenic bacteria and viruses. In the kidney, a recent report has shown that autophagy decreases renal tubular cell apoptosis induced by cisplatin (31) or cyclosporine (32) suggesting the potential protective role of autophagy in cytotoxic injury. However, the role of autophagy in kidney fibrosis, which ultimately leads to ESRD, remains largely unknown.…”
mentioning
confidence: 99%
“…2,16 Considering that TMBIM6, suspected to act as an autophagy enhancer in this study, functionally inhibits BAX, 20,33 the role of BAX in autophagy must be considered. Although neither overexpression of BAX or BAK1 nor ER-targeted BAK1 has been reported to affect autophagy, 34 BAX has been shown to induce autophagy and autophagic cell death.…”
Section: Wwwtandfonlinecommentioning
confidence: 99%
“…13,14 However, CsA-induced autophagy is reported to protect against immunosuppressant-induced nephrotoxicity. 15,16 Lysosomal modulation has been emerged as a regulating approach in autophagy-associated pathological conditions, including nephrotoxicity. 17,18 Lysosome activity and the fusion process contribute to the maintenance and enhancement of autophagy.…”
Section: Introductionmentioning
confidence: 99%